Atrial thrombi occurring during sinus rhythm in cardiac amyloidosis: evidence for atrial electromechanical dissociation. Issue 5 (November 1995) - Dubrey, S.; Pollak, A.; Skinner, M.; Falk, R. H.
Abstract : Thrombus formation in the left atrium is rare in patients in sinus rhythm. In three patients with extensive cardiac amyloidosis transthoracic echocardiography showed large atrial thrombi in or protruding into the body of the left atrium during sinus rhythm. Doppler studies showed no A wave on mitral inflow. Severe atrial and ventricular infiltration by amyloid may have resulted in mechanical atrial standstill with resultant thrombus formation. These findings suggest that patients with severe cardiac amyloidosis may require anticoagulation when atrial function is impaired.